Africapitalism
DOI: 10.1017/9781316675922.003
|View full text |Cite
|
Sign up to set email alerts
|

Africapitalism: A Management Idea for Business in Africa?

Abstract: The efforts to rethink the role of business in development, especially in developing countries, have facilitated the emergence of an array of concepts. Africapitalism -i.e. the private sector's commitment to the socio-economic development of Africa -proposed and championed by Mr. Tony O. Elumelu, is the most recent addition. While the idea of Africapitalism enables a creative space for rethinking business-society relationship from a development perspective in Africa, the failure to clarify what underpins the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 26 publications
0
40
0
Order By: Relevance
“…A recent study by Ibeh et al (in press) identified this “mission‐driven motivation” in one of the internationalizing firms, where the vision of the founders to build a pan‐African organization was the driving force for their intraregional expansion and location decisions. A notable exemplar is Nigerian businessman Tony Elumelu, who has been championing Africapitalism , and urging the African private sector and other Africans to invest in as well as play a transformational role in the region (Amaeshi & Idemudia, ). What makes this trend additionally remarkable is the apparent evolution of the pan‐African vision from a mainly political philosophy driven by national governments and regional agencies to a management orientation increasingly embraced by private‐sector players (Ibeh et al, in press).…”
Section: Internationalization Opportunities For African Firmsmentioning
confidence: 99%
“…A recent study by Ibeh et al (in press) identified this “mission‐driven motivation” in one of the internationalizing firms, where the vision of the founders to build a pan‐African organization was the driving force for their intraregional expansion and location decisions. A notable exemplar is Nigerian businessman Tony Elumelu, who has been championing Africapitalism , and urging the African private sector and other Africans to invest in as well as play a transformational role in the region (Amaeshi & Idemudia, ). What makes this trend additionally remarkable is the apparent evolution of the pan‐African vision from a mainly political philosophy driven by national governments and regional agencies to a management orientation increasingly embraced by private‐sector players (Ibeh et al, in press).…”
Section: Internationalization Opportunities For African Firmsmentioning
confidence: 99%
“…In the Sub-Saharan African context communities play an important role in supporting entrepreneurial activity (Ansari et al 2012;Amaeshi and Idemudia, 2015). Families operating businesses through embedded social relationships internally with family members, and externally with communities and wider stakeholders will use these close social connections to navigate the "institutional voids" in order to mobilise wider networks to access necessary resources and information.…”
Section: An Institutional Perspective On Business Familiesmentioning
confidence: 99%
“…It is even suggested that Ubuntu not only mitigates the individualistic and profit maximization instincts associated with global capitalism but, in fact, that it offers an entirely alternative model for business management (Lutz, ). Recently, Amaeshi and Idemudia (), two leading scholars of CSR in Africa, have suggested that Africa's perennial crisis of development could be perhaps tackled through the promotion of a new concept of “Africapitalism”—a “perspective that is rooted in the values of Ubuntu” (p. 212) and upholds the common good, rather than utilitarian economic calculus, as the core purpose of management.…”
Section: Introductionmentioning
confidence: 99%